Innovative Therapies against Human Glioblastoma Multiforme. (24th July 2011) - Cimini, Annamaria; Ippoliti, Rodolfo
Abstract : Glioblastoma multiforme is the most invasive and aggressive brain tumor in humans, and despite the latest chemical and radiative therapeutic approaches, it is still scarcely sensitive to these treatments and is generally considered an incurable disease. This paper will focus on the latest approaches to the treatment of this cancer, including the new chemicals such as proautophagic drugs and kinases inhibitors, and differentiating agents. In this field, there have been opening new perspectives as the discovery of possible specific targets such as the EGFRvIII, a truncated form of the EGF receptor. Antibodies against these targets can be used as proapoptotic agents and as possible carriers for chemicals, drugs, radioisotopes, and toxins. In this paper, we review the possible mechanism of action of these therapies, with particular attention to the combined use of toxic substances (for example, immunotoxins) and antiproliferative/differentiating compounds (i.e., ATRA, PPAR γ agonists). All these aspects will be discussed in the view of progress clinical trials and of possible new approaches for directed drug formulations.